Comparison of file design, mechanical performance and metallurgical characteristics of premium brands with replica-like endodontic files - Martins, Jorge N.R. (2022)
Objectives: To compare the design, metallurgical characteristics, and mechanical performance between replica-like and premium-brand endodontic instruments. Materials and methods: The instruments of 13 replica-like (Premium Taper Gold, Go-Taper Flex, EdgeTaper, U-File, Go-Taper Universal, Super Files, Multitaper, Pluri Taper, X-Files, One Files, One Files Blue, Reverso Silver, and a ProTaper Next counterfeit) and five premium-brand (ProTaper Universal [PTU], ProTaper Gold [PTG], ProTaper Next [PTN], Reciproc, and Reciproc Blue) systems were compared regarding overall design (stereomicroscopy and scanning electron microscopy), nickel and titanium ratio (energydispersive spectroscopy), phase transformation temperatures (differential scanning calorimetry), and mechanical performance (cyclic fatigue, torsional, and bending tests). Parametric or non-parametric analysis of variance tests were used accordingly for statistical comparisons, with a significance level set at 5%. Results: Globally, the tested instruments were almost equiatomic regarding their elements’ proportion but presented distinct phase transformation temperatures, tip designs, and surface finishing. Additionally, in the PTU F1 files group, Super Files instruments showed a higher time to fracture (130.0 sec) than PTU (44.0 sec) (P<0.05). No significant differences were noted in the maximum torque (P>0.05). Multitaper files had a higher rotation angle (574º) and lower bending resistance (321.4 gf). In the PTG SX instruments group, Go-Taper Flex presented lower maximum torque (0.5 N.cm) and higher bending resistance (582.2 gf) than PTG (0.8 N.cm and 447.1 gf) (P<0.05). No significant differences were observed in the mechanical tests between Premium Taper Gold and PTG (P>0.05). In the PTN group, counterfeits X2 (20.5 sec) and X3 (3.5 sec) showed lower cyclic fatigue strength than PTN (45.5 sec and 40.0 sec) and X-Files (43.0 sec and 35.5 sec) instruments (P<0.05). No difference was noted in maximum torque to fracture (P>0.05). In the reciprocating R25 group, the One Files Blue presented a higher time to fracture (409.6 sec) than Reciproc Blue (223.5 sec) and Reciproc (178.8 sec) (P<0.05). Reverso Silver revealed lower time to fracture and torsional strength. Conclusions: Although replica-like instruments are being marketed as presenting similar characteristics to premium-brand ones, our results suggest marked differences in several of the analyzed variables. Therefore, clinicians may expect some differences in the outcomes.